(untitled) (Global Journal of Medical Research, 2020)
A dental questionnaire survey conducted on 34 high school students, 55 university students, 23 Middle-age who participated in the university festival. Participants answered yes or no to ten self-administered questions. Also, participants described the hardness of meals, brushing teeth after meals, and time to spend eating in a questionnaire. As a result, some students even had some guminflammation. Middle -Ages had many people who had experience with swollen gums (52.2%). Of the participants, the Middle Ages were few who applied fluorine (17.4%), and many were students (high school students 64.7%, university students 90.9%). Most people brush their teeth after breakfast or dinner. Participants replied that they usually eat a little hard (52.0%) or soft (38.1%) food. One high school student replied that he usually eats soft food. The time to eat was longer than breakfast and then dinner, but it was less than 30 minutes ever for dinner. Middle-Ages ad an average time to spend eating of fewer than 10 minutes for breakfast, 14 minutes for lunch, and 22 minutes for dinner. Middle ages had shorter meal times in all than students. Form the results of the participants; we wondered if they did not chew food very well because they eat soft food in a short time.